PRAGMATISME RASIONAL PERKEBUNAN INTI RAKYAT DENGAN MODEL MUDARABAH DALAM MENDUKUNG PENINGKATAN PENDAPATAN MASYARKAT DALAM PANDANGAN EKONOMI SYARIAH: PERKEBUNAN SAWIT - Rendy Syaputra (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Rational pragmatism in the context of smallholder plantation, especially in the palm oil industry, is highly relevant in enhancing community income through an Islamic economic approach. The Mudarabah model, an Islamic economic concept where capital is jointly managed between investors and entrepreneurs with profit-sharing, can serve as the foundation to support income growth in this sector. The application of Mudarabah principles allows small farmers or plantations to partner with core entities or investors. Farmers provide land and labor, while the core company supplies capital in the form of technology, seedlings, and technical guidance. The profit from the harvest is then shared as agreed upon, with the profit distribution based on previously agreed-upon proportions. This enables small farmers or plantations to gain access to capital, technology, and a broader market through partnerships with core companies. As a result, they can improve production yields and the quality of palm oil. The profits obtained from increased production will be shared between both parties according to the Mudarabah agreement. Beyond income enhancement, this approach also encourages risk-sharing between both parties. With mutually beneficial advantages, this model strengthens economic inclusion, empowers farmers, and supports Sharia-compliant economic principles without burdening them with high debt. With a pragmatic and rational approach underlying the Mudarabah model in the palm oil plantation, it can serve as a strong foundation to support fair and sustainable community income enhancement within the framework of Islamic economics.